Effect of Vacuum Sintering Time on Microstructure and Magnetic Properties of Cu/Sn Coating on AlNiCo Permanent Magnetic Material - ZHOU Xiao-yan, LI Dong-ying, ZOU Li-hua, ZHAO Cheng-lin, LI Meng-qi (Cailiao Baohu)
In order to improve the quality of magnetron sputtering Cu/Sn coating on the surface of AlNiCo permanent magnetic material, the coating was treated by vacuum sintering to achieve the purpose of maintaining high magnetism under the premise of strengthening the bonding force. The influence of vacuum sintering time on the microstructure, bonding strength and magnetic properties of Cu/Sn coating was investigated by SEM, universal tensile machine and NIM-2000 analysis system. Results showed that the coating surface quality was better when vacuum sintering time was 1 h. When the time of vacuum sintering was prolonged, the vertical pit structure would be formed and the pit depth would be increased continuously. After vacuum sintering for different times, loose tissue with thickness between 10～12 μm was obtained. When the time of vacuum sintering was prolonged, the binding force between Cu/Sn coating and substrate was also increased. After 1h of vacuum sintering, the binding force reached 21.2 MPa. After increasing the sintering time, the formed smooth interface was less, but the number of pits increased obviously. After the treatment for a longer period of time, the obvious diffusion occurred between the Cu/Sn coating and the matrix, which made the surface ferromagnetic structure transform into a relatively loose structure, resulting in the reduction of coercivity.